Electrochemical behavior of tantalum in potassium hydroxide solutions - Mickova, Irena (International Association of Physical Chemists (IAPC), 2018)
The electrochemical behavior of tantalum in various concentrations of KOH solutions (0.1 M -10 M), was investigated using the evolution of the open circuit potentialin time, cyclic voltammetry and ellipsometricmeasurements. Depending on KOH concentrations, the open circuit potential measurements have shown three distinct behaviors concerning oxide film formation on the electrode surface and its dissolution. The cyclic voltammetry measurements were performed in various potential ranges, from -1.4 to 8 V, different concentrations of KOH solutions (0.110 M) and sweep rates ranging from 0.005 V/s to 1 V/s. In the passive region, very stable passive films were formed, which reduction has not been possible during cathodic polarization even at highly concentrated KOH solutions. In the trans-passive region, the very strong peak at 1.65 V was monitored, which nature and chemical composition is still not well known.
Keywords: Ta; KOH; open circuit potentials; cyclic voltammetry; ellipsometry